Experimental methodology for TiNi shape memory alloy testing under complex stress state - Raniecki, B.; Dietrich, L.; Kowalewski, Z.L.; Socha, G.; Miyazaki, S.; Tanaka, K.; Ziółkowski, A. (Archives of Mechanics, 1999)
The experimental method and preliminary results of multiaxial proportional loadings at a range of different temperatures are discussed for the TiNi shape memory alloy. The results are limited to the R-phase reorientation and transformation pseudoelasticity of the material tested at the selected constant temperatures. The main objective of the paper is to develop experimental knowledge of the shape memory alloy properties under complex stress states which would allow better understanding of the material behaviour and create a basis for theoretical modelling.